Association of insulin regimens with severe hypoglycaemia in patients with type 1 diabetes: A Danish case–control study. Issue 8 (6th March 2020) - Jensen, Morten Hasselstrøm; Hejlesen, Ole; Vestergaard, Peter
Abstract : Aims: To evaluate the risk of severe hypoglycaemia for patients with Type 1 diabetes (T1D) when exposed to insulin regimens including human insulin only or insulin analogues. Methods: A total of 19 896 patients with T1D were extracted from the Danish National Patient Register. Of these, 6379 T1D patients experiencing 1 of more severe hypoglycaemic episodes (total of 17 242 episodes) were matched 1:1 with T1D patients without severe hypoglycaemia. A logistic regression model with last insulin regimen used as exposure was constructed to analyse the effect on severe hypoglycaemia. Results: People on a basal–bolus regimen with insulin analogues had a reduced risk of severe hypoglycaemia of 39% (odds ratio: 0.61, 95% confidence interval: 0.54–0.68) compared to patients on a basal–bolus human insulin only regimen. Furthermore, patients on a premixed regimen containing an insulin analogue had a 58% (odds ratio: 0.42, 95% confidence interval: 0.36–0.49) reduced risk of severe hypoglycaemia compared to patients on premixed human insulin only. Conclusion: This study indicates that use of a basal–bolus insulin regimen with an insulin analogue is safer with respect to severe hypoglycaemia in patients with T1D than the use of a basal–bolus human insulin only regimen.